Konsep Pendidikan Tauhid menurut K.H. Abdullah Sa’id - Suyatman, Suyatman; Supono, Eko; Mulyanto, Mulyanto (TSAQOFAH, 2025)
This article discusses the concept of tauhid education according to Ustadz Abdullah Said, founder of Pondok Pesantren Hidayatullah, who regarded tauhid as the primary foundation for building a strong Muslim aqidah, morality, and character. Abdullah Said developed the Sistematika Nuzulnya Wahyu (SNW) method, based on the sequence of the first five revelations received by Prophet Muhammad SAW (QS Al-‘Alaq 1–5, Al-Qalam 1–7, Al-Muzzammil 1–10, Al-Muddatsir 1–7, and Al-Fatihah 1–7). Each surah contains fundamental principles for forming an Islamic personality, namely awareness of Allah, a Qur’anic life vision, spiritual strengthening, readiness for dakwah, and a complete orientation toward worship. This holistic approach integrates tilawah, tazkiyah, and ta’limah, aiming to produce dakwah cadres who have faith, Qur’anic morals, active worship, and commitment to the jamaah. The concept is applied in the pesantren environment by combining dimensions of worship, social engagement, and economic activities, thus shaping agents of change ready to contribute to society.